Foreign Experience of Ensuring Human Rights during Recruitment of the Armed Forces as an Element of the State’s National Security - Zaporozhchenko, Yuliia; Kononets, Vita; Kumeiko, Andrii; Lemekha, Rostislav; Pysmennyi, Oleksandr (Syariah: Jurnal Hukum dan Pemikiran, 2024)
The purpose of the article is to carry out an original study of the main aspects of ensuring human rights during recruitment of the armed forces as an element of the state’s national security. Four methods of recruitment (manning) of armed forces have been established in the world, namely: on the basis of general military duty - by conscription of citizens for military service; on a voluntary basis - by recruiting military personnel under a contract; mixed - on the basis of the law on general military duty and voluntary recruitment of servicemen under contract; police method - on the basis of the law on the general military conscription. This article is the qualitative research with a historical and comparative approach. It was concluded that the main argument of supporters of a professional army in the world consists in the following: firstly, professional possession of military equipment in conditions of the digital development of society, and secondly, motivation of military personnel to complete military service. Currently, most developed countries such as the United States of America (USA), France, Israel, Germany, Poland, the Czech Republic, and Switzerland adhere to the course of professionalizing their armed forces and recruit their armies on a voluntary basis.